Emergence of Postmodernism After World War II Characteristics of Being - Mirzoulug, Mamasaliev (Pubmedia Social Sciences and Humanities, 2025)
This article examines the emergence and development of postmodernism as a literary and cultural movement following World War II. Postmodernism is characterized by its departure from modernist principles, embracing fragmentation, irony, black humor, and metafiction. The study investigates the philosophical underpinnings of postmodernism through prominent theories such as deconstruction and poststructuralism, drawing on works of key figures like Derrida, Lyotard, and Baudrillard. Methodologically, the analysis focuses on thematic and stylistic elements, emphasizing how postmodern literature questions traditional narratives, linearity, and universal truths. The findings reveal that postmodernism’s complexity and ambiguity reflect a critique of contemporary societal norms and values. Despite its challenges, such as inaccessibility and intricate structures, postmodern literature offers profound insights into human existence and societal constructs, making it a pivotal movement in cultural history. This article aims at analyzing postmodernism, the literary movement that emerged after the World War II, the factors influenced to its emergence, the main peculiarities of postmodernism and its impact on various areas of society and the reflection of the postmodernism in the works of contemporary writers have been investigated.